2019
DOI: 10.1080/21655979.2019.1599628
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation effects of medial forebrain bundle micro-electrical stimulation

Abstract: Brain micro-electrical stimulation and its applications are among the most important issues in the field of brain science and neurophysiology. Deep brain stimulation techniques have been used in different theraputic or alternative medicine applications including chronic pain control, tremor control, Parkinson's disease control and depression control. Recently, brain electrical stimulation has been used for tele-control and navigation of small animals such as rodents and birds. Electrical stimulation of the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It is important to note that the period of electrical stimulation was limited to the experimental session, and no other intervention was conducted between weeks. A previous study indicated that continuous stimulation can lead to changes in the characteristics of the medial forebrain bundle (MFB) due to adaptation [ 24 ], which necessitates further investigation of the effects of continuous application of our system.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the period of electrical stimulation was limited to the experimental session, and no other intervention was conducted between weeks. A previous study indicated that continuous stimulation can lead to changes in the characteristics of the medial forebrain bundle (MFB) due to adaptation [ 24 ], which necessitates further investigation of the effects of continuous application of our system.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their excellent biocompatibility and compliance with resistance and toughness requirements, metal microelectrodes are widely applied in animal robotics research. For rat robots, the electrical stimulation sites investigated mainly encompass the MFB, which is used to elicit virtual rewards and propel rats forward [23], and the SIBF, ventral posteromedial nucleus (VPL), ventral posteromedial nucleus (VPM) [24], and nigrostriatal pathway (NSP) [25,26], which are utilized for left-right turning control. Therefore, the implantation of electrodes is required at multiple stimulation sites.…”
Section: Introductionmentioning
confidence: 99%
“…Psychologically, the MFB is considered to serve as the neural substrate for motivation and pleasure, and thus, stimulation of the MFB and surrounding regions has been behaviorally used as a neural and “virtual” reward ( Olds and Milner, 1954 ; Margules and Olds, 1962 ; Beninger et al, 1977 ). MFB stimulation ignites hedonic feelings and elicits pleasant bodily sensations in animals, thus highly motivating them to perform a variety of operant and spatial tasks ( Carlezon and Chartoff, 2007 ; Lee et al, 2010 ; Sun et al, 2012 ; Farakhor et al, 2019 ; Kong et al, 2019 ). Electrical stimulation of the reward system, including the MFB, has also allowed for (tele)control of the spatial navigation of rodents and birds ( Talwar et al, 2002 ; Sun et al, 2012 ; Huai et al, 2016 ; Khajei et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%